Post‐prostatic‐massage urine exosomes of men with chronic prostatitis/chronic pelvic pain syndrome carry prostate‐cancer‐typical microRNAs and activate proto‐oncogenes. Issue 3 (17th November 2022) - Schneider, Laura; Dansranjav, Temuujin; Neumann, Elena; Yan, Hang; Pilatz, Adrian; Schuppe, Hans‐Christian; Wagenlehner, Florian; Schagdarsurengin, Undraga
Abstract : Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) has a high prevalence of up to 15% and accounts for 90–95% of prostatitis diagnoses, and yet its etiopathogenesis and link to prostate cancer (PCa) are still unclear. Here, we investigated microRNAs in exosomes isolated from blood and post‐prostatic‐massage urine of CP/CPPS type IIIb patients and healthy men. THP‐1 monocytes (human leukemia monocytic cell line) were treated with exosomes and subjected to mRNA arrays "Cancer Inflammation and Immunity Crosstalk" and "Transcription Factors." Using The Cancer Genome Atlas, the expression of CP/CPPS‐associated microRNAs was analyzed in PCa and normal prostate tissue. In silico functional studies were carried out to explore the disease ontology of CP/CPPS. In CP/CPPS, urine exosomes exhibited significant upregulation of eight PCa‐specific microRNAs (e.g., hsa‐miR‐501, hsa‐miR‐20a, and hsa‐miR‐106), whose target genes were significantly enriched for GO terms, hallmark gene sets, and pathways specific for carcinogenesis. In THP‐1 monocytes, CP/CPPS‐derived urine exosomes induced upregulation of PCa‐associated proinflammatory genes (e.g., CCR2 and TLR2 ) and proto‐oncogene transcription factors (e.g., MYB and JUNB ). In contrast, CP/CPPS‐derived blood exosomes exhibited molecular properties similar to those of healthy men. Thus, CP/CPPS exhibits molecular changes that constitute a risk for PCa and should be considered in the development of PCa biomarkers and cancer screening programs. Abstract : Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) has a high incidence. However, its risk for prostate cancer (PCa) is unexplored. Findings: exosomes in post‐prostatic‐massage urine of CP/CPPS patients exhibited Pca characteristic microRNA profiles and activated cancer‐associated proinflammatory and proto‐oncogene transcription factors in THP‐1 monocytes. Thus, CP/CPPS may represent a risk for PCa development and should be considered in cancer screening programs.